Faktor Faktor Yang Mempengaruhi Akuntabilitas Kinerja Instansi Pemerintah Kota Pekanbaru - Yolanda Citra; Muhammad Ahyaruddin; Siti Samsiah (LPPM Universitas Sains dan Teknologi Komputer, 2026)
This study aims to analyze the influence of leadership style, compliance with laws and regulations, human resource quality, performance-based budgeting, and performance evaluation on the performance accountability of government agencies. This study uses a quantitative approach with a survey method by distributing questionnaires to 96 respondents who are employees of Regional Work Units (SKPD). The data analysis technique used is Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results show that leadership style and performance evaluation do not affect the performance accountability of government agencies. Meanwhile, compliance with laws and regulations, human resource quality, and performance-based budgeting have a positive and significant effect on the performance accountability of government agencies. These findings indicate that increased performance accountability is more influenced by compliance with regulations, apparatus competence, and the implementation of a performance-based budgeting system compared to leadership and performance evaluation factors. This study is expected to contribute to government agencies in improving the quality of performance management and public accountability. Keywords: Leadership Style, Regulatory Compliance, Human Resource Quality, Performance-Based Budgeting, Performance Evaluation, Performance Accountability